PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII6 SMP NEGERI 25 PEKANBARU - Irma Widya Lisa; Kartini '; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This reseacrh based on the students math ability class VIII6 of SMPN 25 Pekanbaru under Minimum Mastery Criteria  with a percentage of 32,50% and the learning process still teacher center. The research was classroom action research. This research aims to improve learning process and outcomes students by implementing cooperative learning model type of Think Pair Square. There are 40 students in the class, consisting 14 girls and 26 boys. The technic of data collection on this research are observation sheets and math achievement tests. The observation sheets are analyze in qualitative descriptive way, while the math achievement tests are analyze in quantitative descriptive way. The qualitative analysis showed an improvement of learning process prior to the action of the first cycle to the second cycle. Then the result of this research showed an increase in students from the base score with the percentage 32,50% to 42,50% on the first daily test and 65% on the second daily test. From the results of this study concluded that Cooperative Learning model type of Think Pair Square can improve the students’ learning achievement at class VIII6 of SMPN 25 Pekanbaru in the first semester academic years 2016/2017.